EFFECTS OF REDUCE SPECIFIC BAU ON KUNASIT (Curcuma Domestica Val.) AS NATURAL DYE COLOR - Mardiah, Mardiah; Nurhayati, Astri; Amalia, Lia (Universitas Djuanda, 2018)
Turmeric is widely used as a herbal medicine, food preservation and food coloring. However, food industries have less interest to utilize turmeric as a food coloring due to its spesific aroma. The objective of this research was to obtain the proper method to eliminate the turmeric’s spesific aroma. The experimental methods consisted of 3 stages, namely distillation (A1) and non-distillation (A2) methods which then was extracted by maceration method with the addition of 96% ethanol (B1), acetone (B2) and ethanol 96% + acetone (B3) as stage 1; with (C1) and without heating (C2) as stage 2; and the addition of 3% acetic acid and 3% citric acid as stage 3. The results of stage 1, 2, and 3 were the spesific aroma of turmeric tend to be weak when use the distillation and maceration with 96% ethanol where the curcumin content was 0.50%, and with the addition of 3% acetic acid which have a brighter color, respectively. The color analysis showed that the color by adding 3% acetic acid has CIE b* (yellow) of 66.85 with pH of 3.24. So, the proper method for eliminating the turmeric’s spesific aroma was distillation process then followed by extraction using 96% ethanol and adding 3% acetic acid to increase the color brightness and homogeneity.